HIGH-TECH PRODUCTION OF PHOTO-ENERGY IN KAZAKHSTAN BASED ON THE SARYKOL QUARTZ DEPOSIT - D. Kalygulov; I. Klinovitskaya; T.Turmagambetov; A. Pavlov; S. Plotnikov; B. Mukashev; A. Serikkanov; Zh. Agabekov; D. Kantarbaeva (Academic Scientific Journal of Computer Science, 2019)
The technology of silicon purification to solar grade silicon for metallurgical silicon obtained from the Sarykol quartz deposit by carbothermic reduction is presented. This technology is based on metallurgical methods of purification, namely gas-slag refining and directional crystallization. Silicon ingots are grown from the solar grade silicon using "monolike" technology. Photovoltaic converters are manufactured and investigated. Solar cells from "monolike" silicon have a higher efficiency of 17-18.4%, in comparison with solar cells made from multicrystalline silicon. Converters with high efficiency were tested for the light-induced degradation effect.